Testing nonlinear convergence in Malaysia - Habibullah, Muzafar Shah; Awang Marikan, Dayang Afizzah; Liew, Venus Khim Sen; Lim, Kian Ping (Penerbit Universiti Kebangsaan Malaysia, 2013)

(untitled)
The purpose of the present paper is to examine income convergence in Malaysia by using the nonlinear unit root test due to Kapetanios et al. (KSS, 2003) and extended by Chong et al. (CHLL, 2008) to permit the test of long-run convergence and catching-up hypotheses. We apply the KSS-CHLL nonlinear unit root for the test of nonlinear convergence between thirteen states with respect to Wilayah Persekutuan (the riches state) of Malaysia for the period 1965 to 2003. Generally, our results suggest that out of the thirteen states, only Kedah, Negeri Sembilan, Perak, Perlis and Selangor support the long-run convergence hypothesis while Johor, Kelantan, Melaka, Pahang and Penang suggest catching-up. Lastly, Sabah, Sarawak and Terengganu indicate income divergence from Wilayah Persekutuan.